Impaired Mitochondrial Biogenesis Precedes Heart Failure in Right Ventricular Hypertrophy in Congenital Heart Disease - Karamanlidis, Georgios (2011)
BACKGROUND: The outcome of the surgical repair in congenital heart disease (CHD) correlates with the degree of myocardial damage. In this study we determined whether mitochondrial DNA depletion is a sensitive marker of right ventricular (RV) damage and whether impaired mitochondrial DNA (mtDNA) replication contributes to the transition from compensated hypertrophy to failure. METHODS AND RESULTS: RV samples obtained from 31 patients undergoing cardiac surgery were compared to 5 RV samples from non-failing hearts (control). Patients were divided into compensated hypertrophy and failure groups based on preoperative echocardiography, catheterization and/or MRI data. Mitochondrial enzyme activities (citrate synthase and succinate dehydrogenase) were maintained during hypertrophy and decreased by ~40% (p<0.05 vs. control) at the stage of failure. In contrast, mtDNA content was progressively decreased in the hypertrophied RV through failure (by 28±8% and 67±11% respectively, p<0.05 for both), whereas mtDNA encoded gene expression was sustained by increased transcriptional activity during compensated hypertrophy but not in failure. MtDNA depletion was attributed to reduced mtDNA replication in both hypertrophied and failing RV and it was independent of PGC-1 down-regulation but was accompanied by reduced expression of proteins constituting the mtDNA replication fork. Decreased mtDNA content in compensated hypertrophy was also associated with pathological changes of mitochondria ultrastructure. CONCLUSIONS: Impaired mtDNA replication causes early and progressive depletion of mtDNA in the RV of the CHD patients during the transition from hypertrophy to failure. Decreased mtDNA content is likely a sensitive marker of mitochondrial injury in this patient population.